2021
DOI: 10.3390/biomedicines9121772
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation Induced by Sitagliptin: A New Strategy for Treating Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR) involves progressive neurovascular degeneration of the retina. Reduction in synaptic protein expression has been observed in retinas from several diabetic animal models and human retinas. We previously reported that the topical administration (eye drops) of sitagliptin, a dipeptidyl peptidase-4 (DPP-4) inhibitor, prevented retinal neurodegeneration induced by diabetes in db/db mice. The aim of the present study is to examine whether the modulation of presynaptic proteins is a mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In the present study, we demonstrated the antioxidant and the anti-inflammatory properties of sitagliptin, a DPP-4i, in an experimental model of DR. These findings support and reinforce previous evidence showing the beneficial effects of topical administration of sitagliptin in early stages of DR [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we demonstrated the antioxidant and the anti-inflammatory properties of sitagliptin, a DPP-4i, in an experimental model of DR. These findings support and reinforce previous evidence showing the beneficial effects of topical administration of sitagliptin in early stages of DR [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the search for new treatments targeting the earliest and asymptomatic stages of DR at the onset of NVU impairment is an unmet medical need that has to be urgently addressed [ 11 ]. In this context, a new therapeutic strategy is the topical administration (eye drops) of dipeptidyl peptidase-4 (DPP-4) inhibitors (DPP-4i), which have demonstrated promising results in experimental models of DR [ 12 , 13 ]. Through the nondegradation of glucagon-like peptide-1 (GLP-1), the main target of the DPP-4 enzyme, and through other independent and not clearly elucidated mechanisms, DPP-4i significantly prevents the appearance of the main hallmarks of DR, glial activation, and neuronal cell death, as well as preserving the functionality of the retina [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, sitagliptin was administered orally, and the effects can be attributed to the systemic improvement due to the lowering of blood glucose levels. Nevertheless, our group demonstrated that sitagliptin eye drops are able, in a non-glycaemia-dependent fashion, to significantly prevent the diabetes-induced synaptic failure that occurred in the retina of db/db mice, evidencing the intrinsic neuroprotective properties of DPP-4i [15]. Considering these previous studies, the GSEA results obtained reveal that, among the different beneficial effects of DPP-4i in DR models, retinal neuroprotection is the most relevant one.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, sitagliptin has beneficial effects on diseases derived from complications of diabetes mellitus, such as ischaemic heart disease [ 34 ], atherosclerosis, and hypertension [ 35 ]. Sitagliptin also appears to be useful in the initial treatment of microangiopathic complications of diabetes, such as diabetic retinopathy [ 36 , 37 , 38 ] and diabetic nephropathy [ 39 ], in experimental models. In addition, sitagliptin appears to have pleiotropic effects, including effects on COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%